Regulatory T cells in human lymphatic filariasis: stronger functional activity in microfilaremics. - Linda J Wammes; Firdaus Hamid; Aprilianto E Wiria; Heri Wibowo; Erliyani Sartono; Rick M Maizels; Hermelijn H Smits; Taniawati Supali; Maria Yazdanbakhsh (Public Library of Science (PLoS), 2012)
Infection with filarial parasites is associated with T cell hyporesponsiveness, which is thought to be partly mediated by their ability to induce regulatory T cells (Tregs) during human infections. This study investigates the functional capacity of Tregs from different groups of filarial patients to suppress filaria-specific immune responses during human filariasis. Microfilaremic (MF), chronic pathology (CP) and uninfected endemic normal (EN) individuals were selected in an area endemic for Brugia timori in Flores island, Indonesia. PBMC were isolated, CD4CD25(hi) cells were magnetically depleted and in vitro cytokine production and proliferation in response to B. malayi adult worm antigen (BmA) were determined in total and Treg-depleted PBMC. In MF subjects BmA-specific T and B lymphocyte proliferation as well as IFN-gamma, IL-13 and IL-17 responses were lower compared to EN and CP groups. Depletion of Tregs restored T cell as well as B cell proliferation in MF-positives, while proliferative responses in the other groups were not enhanced. BmA-induced IL-13 production was increased after Treg removal in MF-positives only. Thus, filaria-associated Tregs were demonstrated to be functional in suppressing proliferation and possibly Th2 cytokine responses to BmA. These suppressive effects were only observed in the MF group and not in EN or CP. These findings may be important when considering strategies for filarial treatment and the targeted prevention of filaria-induced lymphedema.